Potentials of Adansonia digitata linn. Seed and Leaf: Proofs from Two Provenances and Implications for Human Diet - Bidemi, K. Suleiman; Iroko, Olayinka Ajani; Salami, D. Kaseem; Jibo, A. Umar (Journal of Science Research and Reviews, 2026)
This study aims to assess the nutritional contents of Adansonia digitata (Linn) seeds and leaves from two provenances. The prevalence of malnutrition and nutrient deficiencies, particularly in developing regions, and the underutilization of baobab's nutritional potential. The study seeks to explore the nutritional value of baobab seeds and leaves and their contribution to human diet. Study was conducted at the Nutrition Laboratory of Biochemistry complex, Federal University Dutse, Jigawa State. Samples of Adansonia digitata leaf and seed were collected from two locations (Dutse, Jigawa and Ilorin, Kwara). Purposive sampling was used to select the communities and mother trees. Parameters such as moisture, ash, fat, protein, carbohydrate, and crude fibre were assessed. Data was analyzed using descriptive statistics and t-test to compare the nutritional content of seeds and leaves. The results showed significant variations in moisture, ash, fat, protein, carbohydrate, and crude fibre content among the samples. Results revealed that Ilorin seeds and leave had the highest moisture (9.217±0.617), (6.159±0.541), protein content (20.235±0.946), (14.219±0.675) Fat (13.846±1.078), (2.797±0.619), while Dutse seeds and leave had the highest carbohydrate content (59.299±1.295), (77.641±0.910) and crude fibre respectively. Adansonia digitata seeds and leaves from Dutse and Ilorin exhibit notable nutritional variations influenced by provenance. Ilorin samples showed higher moisture, protein, and fat contents, while Dutse samples were richer in carbohydrates and crude fibre. These findings highlight the plant’s nutritional versatility. It is recommended that both provenances be promoted for dietary use, while further studies should explore environmental factors affecting nutrient composition and support their inclusion in food and nutrition programs.
Keywords: Potentials; Adansonia digitata; Seed; Leaf; Human Nutrition